2018
DOI: 10.33738/spo.v16i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Association between the mode of delivery and the occurance of early childhood caries in children from 2 to 5 years of the maternal chilhood center Pachacutec Perú-Korea, Diresa Callao, Perú 2016

Abstract: Early childhood caries (ECC) continues to be the biggest oral health problem in developing countries. Several studiesreport ECC prevalence in children aged 3 years from 40% to 65.7% and in children 5 and 6 years of age up to86%. There are multiple risk factors associated with ECC, such as: cariogenic diet, poor oral hygiene, low salivaryflow, low parental socioeconomic status, low parental education, etc. But there is also a “mode of delivery” factorthat is not being considered and could be important and deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There was a considerable inconsistency between the studies. The prevalence of ECC was significantly higher ( p < 0.05) among the C-section children in five studies (Peretz and Kafka 1997 ; Pattanaporn et al 2013 ; Garcia-Castro and Perona-Miguel de Priego 2017 ; Boustedt et al 2018 ; Shanthosh Raj et al 2018 ) and four reported no significant difference between the two modes of delivery (Barfod et al 2012 ; Zhou et al 2013; Sridevi et al 2018 ; Korolenkova et al 2020 ). One study found significantly more caries in the vaginal group (Brandquist et al 2017 ) but the caries prevalence was very low in both groups.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…There was a considerable inconsistency between the studies. The prevalence of ECC was significantly higher ( p < 0.05) among the C-section children in five studies (Peretz and Kafka 1997 ; Pattanaporn et al 2013 ; Garcia-Castro and Perona-Miguel de Priego 2017 ; Boustedt et al 2018 ; Shanthosh Raj et al 2018 ) and four reported no significant difference between the two modes of delivery (Barfod et al 2012 ; Zhou et al 2013; Sridevi et al 2018 ; Korolenkova et al 2020 ). One study found significantly more caries in the vaginal group (Brandquist et al 2017 ) but the caries prevalence was very low in both groups.…”
Section: Resultsmentioning
confidence: 91%
“…The main characteristics are listed in Table 1 . Six studies were cross-sectional trials (Zhou et al 2011 ; Garcia-Castro and Perona-Miguel de Priego 2017 ; Shanthosh Raj et al 2018 ; Pattanaporn et al 2018; Sridevi et al 2018 ; Korolenkova et al 2020 ), two utilized population registers (Barfod et al 2012 ; Brandquist et al 2017 ), one was based on a prospective birth cohort (Boustedt et al 2018 ) and two had a case–control design (Peretz and Kafka 1997 ; Nakai et al 2016 ). The number of participating children per study ranged from 100 to 55,092 with a median value of 352.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations